(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
This research studies two complementary aesthetic values, one of which is the value of (beauty), which is a basic value of the values ​​on which aesthetics is based, and the other is the value of (tenderness), which is a subsidiary value, based on the basic value, and is derived from it, and does not contradict it, and is distinguished - after that – in characteristics earned by its own subtle features. These two values ​​are available in several scenes of life that are conveyed by poetry and transformed into artistic scenes. This research will suffice to study them in the painting of the woman specifically, in examples from the poetry of the veteran Bedouin poets, whose poems have not been studied sufficiently, even if they were collected, investigated and published, to be a material upon which studies are built that deal with them from various artistic and intellectual angles. The purpose of the research is to show the parameters of the values ​​of the beautiful and the gentle, and how each of them is formed intellectually and artistically in the studied examples, and to show the extent of the stability of the pre-Islamic model that is the ideal of beauty and tenderness for veteran poets and poets of later eras, or its change - if a change is noticed in it - during the formation of each of the two values ​​and their employment, and the reasons for that.